Theory and Practice of the Post-Audit of Capital Projects: Evidence from the Czech Republic - Kovárník, Jaroslav; Hamplová, Eva; Lefley, Frank (My University, 2022)
This paper reports on the post-audit practices of organisations in the Czech Republic. Much of the earlier published empirical research has been conducted in Australia, Canada, the USA, and Western Europe. Only recently, attention has been given to emerging markets, including Eastern European accession/transition countries. This exploratory study's main objective is to identify CZ companies' post-audit practices and obtain opinions on various post-audit issues. It also seeks to assess if these practices mirror those adopted by more developed economies. The research adopts interview, questionnaire, and descriptive statistical analysis approaches. The results present some interesting findings which are of value to both academics and practitioners. Although at the fringe of the general understanding of logistics, project management is a vital part. The authors believe that this is one of the first papers to focus on CZ post-audit practices and fills an important gap in the applied logistics literature.
Teorie a praxe post-auditu kapitálových projektů: evidence z České republiky
Keywords: capital budgeting; Czech Republic; investment appraisal; logistic infrastructure; post-audit; post completion audit; project management; financování projektů; Česká republika; hodnocení investic; logistická infrastruktura; post-audit; následné hodnocení; projektový management